The use of screencasting in higher education: a case study - Abdija, Jetmir; Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari (Partridge Publishing Singapore, 2018)
Screencasting is a powerful instructional tool for learning, yet few in higher education take advantage of its utility. This book showcases the benefits of screencasting and how it can facilitate students’ acquisition of complex content, like statistics. It is a condensed version of a case study that examined the effects of screencasts on postgraduate students’ learning of advanced statistics. Every chapter guides the reader through the intricate process of conducting the research and gives a complete picture of the design, materials, and instrumentation. If you are a novice researcher and are interested in technology, this book is for you.